CHARACTER EDUCATION IN DANCE DRAMA ‘SECOND CHANCE’ - Ni Wayan Mudiasih; I Ketut Sumerjana; Kadek Diah Pramanasari (International Journal of Social Science, 2025)
The dance drama ‘Second Chance’ is a work adapted from the Srimad Bhagavatam book which tells the story of Ajamila, a man who initially lived in virtue but then fell into a life full of sin before finally finding a way to redemption. This dance drama not only presents a spiritual story, but also contains deep character education values. This paper aims to analyze how the elements in the dance drama ‘Second Chance’ depict the principles of character education, including regret, repentance, and behavioral change. In addition, this study also attempts to identify the values ​​of character education and moral messages contained in the dance drama. Through a qualitative approach with text analysis and direct observation, this paper shows how the dance drama ‘Second Chance’ can function as an effective tool in teaching character values ​​to the audience. The results of this paper show that the dance drama "Second Chance" depicts the principles of character education through elements such as personal change, love, regret, forgiveness, prayer, conflict, and integrity. The values ​​of character education contained include religious, honesty, responsibility, tolerance, as well as being friendly and communicative. This drama also conveys a moral message that everyone has the opportunity to change and correct mistakes.